Who are faculty assessment leaders?. Issue 6 (18th August 2022) - Gordon, Sarah; Smith, Elizabeth
Abstract: The role of faculty in gathering, analyzing and using student learning data is growing and changing, but still underrepresented in the higher education research literature. While faculty are often expected and required to participate in assessment work, some faculty go beyond assessment work as service to take leadership roles. Using data collected and analyzed through a multi-phase exploratory sequential mixed methods research design, we combine data from administrator surveys, faculty interviews and analysis of faculty CVs to describe the role of faculty who take leadership roles in assessment work on their campuses: faculty assessment leaders. In this paper, we examine how faculty assessment leaders came to the role, if and how they were trained or prepared for the role, and how they describe their work. We recommend that institutions who seek to promote faculty engagement in assessment take a strategic approach to developing faculty assessment leaders, providing them with training and recognizing and rewarding their leadership.